The Effects of Family Support and Personal Income on Life Satisfaction: Literature - Guo Meibo; Alyaa Afifah Abu Talib (Journal of Current Research and Studies, 2025)
Purpose: This study systematically reviewed and sorted out the relevant studies on the impact of personal income and family support on life satisfaction, aiming to explore the correlation among them, and propose some feasible measures to improve people's life satisfaction based on the research results and practical problems or specific fields. Design/methodology/approach: The methods of literature review and qualitative research were used in this study. Findings: The research review found that both personal income and family support have a positive impact on life satisfaction. Research limitations: The literature review can only be analyzed based on existing research results, and cannot provide new data or findings. There may be bias in the selection of literature, and it is easy to overlook some studies that are not easy to obtain but are equally important. Practical implications: The impact of family support and personal income on life satisfaction can help social workers and policymakers better identify and address well-being issues among residents, especially during difficult economic times. Research on this topic can also help to assess the impact of family support and personal income in different socioeconomic contexts. value: Through sorting out the existing research, we can clearly show the research context and development trend in this field. On the basis of reviewing the existing research, the shortcomings and gaps of the current research are further identified to provide direction and inspiration for future research.